The Global Sixties at the University of La Plata. Peripheral readings and crosscirculations (Argentina, 1968-1971) - Pis Diez, Nayla (CIAN-Revista de Historia de las Universidades, 2024)
This paper presents a debate about the circulation of ideas, repertoires and flags of action in the framework of the «global sixties», from the point of view of the contemporary actors to the phenomenon. In this way, (1) we will critically frame ourselves in the field of studies around the protests that took place in not a few parts of the globe during 1968 and the decade that contains it, (2) recovering actions, readings and political positions of the protagonists: activists, teachers and university students/ ace of La Plata city. That is, trying to reconstruct empirically how the same actors thought and explained that cycle.
Keywords: student movement; Argentina; Global 68; transnational circulations